PENENTUAN DISOLUSI PADA OBAT SENYAWA KETOPROFEN SECARA SPEKTROFOTOMETRI - Futeri, Renny; Riani, Pevi (JURNAL KIMIA SAINTEK DAN PENDIDIKAN, 2023)
Research on dissolution determination of Ketoprofen compounds by Spectrophotometry. Ketoprofen is a non-steroidal anti-inflammatory drug compound (NSAID) that works as an anti-inflammatory. Anti-inflammatory here is a group of drugs used to reduce inflammation and relieve pain. The dissolution test is a method used to determine the content of active compounds that dissolve in drugs, where the time, temperature and media are set according to the human stomach and intestines, and can find out how much the content of active compounds dissolves in the human intestines and stomach. This dissolution test, then the ketoprofen drug is read by spectrophotometry. Test the dissolution by spectrophotometer at a wavelength of 260 nm using HCl 0.1 N and buffer pH 7.4. The results of the determination of the dissolution test of the active substance on ketoprofen at the acid stage obtained an average of 0.009% and at the pH 7.4 buffer stage obtained an average content of 86.4155%. It can be concluded that the determination of the ketoprofen dissolution test in the sample meets the requirements (MS), in accordance with the specifications of the Internal Standard of PT Novell Pharmaceutical Laboratories, namely at the acid stage not more than 10% of ketoprofen dissolved in 2 hours, and at the pH 7.4 buffer stage it has a requirement of 75%. ketoprofen dissolved in 45 minutes. In the dissolution of acidic media, 0.1 N HCl is used because its condition resembles that of the stomach.